Empowering Edupreneurship through AI-Based Creative Journalism Education - Hayatun Nufus; Subyantoro; Hari Bakti Mardikantoro; Rahayu Pristiwati; Henry Zainarthur (CORISINTA, 2025)
The advancement of Artificial Intelligence (AI) has reshaped journalism and education, creating opportunities to strengthen creative writing and entrepreneurial skills. AI-driven journalism platforms, such as automated content generation and real-time feedback, empower students to become both skilled writers and edupreneurs, while developing 21st-century competencies including creativity, critical thinking, collaboration, and digital literacy. This study examines the influence of AI integration on creative writing skills, edupreneurship, and competency development using a quantitative research design. Data were collected through structured questionnaires distributed to university students and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The analysis revealed high reliability and convergent validity of the measurement model, with structural results confirming significant positive relationships between AI integration and creative writing skills, and between creative writing skills and 21st-century competencies. Furthermore, creative writing was shown to mediate the connection between AI adoption and both entrepreneurship and competency development, indicating its key role in linking technological tools with educational and entrepreneurial outcomes. The findings underline the transformative role of AI in journalism education, not only in enhancing writing proficiency but also in building entrepreneurial capacity and essential future-ready skills. This research provides practical implications for integrating AI literacy, creative expression, and entrepreneurship into curricula, while also aligning with Sustainable Development Goals (SDGs) such as Quality Education, Economic Growth, Innovation, and Global Partnerships, supporting inclusive and technology-driven learning.